PELATIHAN DAN PENDAMPINGAN GURU MATEMATIKA DALAM PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS ETHNOMATHEMATICS PADA PEMBELAJARAN MATEMATIKA SMP DI KARTASURA JAWA TENGAH - Toyib, Muhamad; Faiziyah, Nuqthy; Sutarni, Sri; Hasan, Titis Rohmat (Jurnal Terapan Abdimas, 2023)
Abstract. This community service is aimed at: (a) introducing how to design ethnomathematics-based student worksheets in mathematics learning for teachers of Muhammadiyah Junior High School in Kartasura;(b) holding workshops and training teachers in designing ethnomathematics-based student worksheets. The training was conducted online using Zoom meetings and Schoology Learning Management System. The participants were teachers of Muhammadiyah Junior High School in Kartasura. It was done through phases as follows: preparation, consisting of internal and external coordination; the implementation phase which covers the introduction and training of ethnomathematics-based students worksheets designed in mathematic learning. 17 teachers from Muhammadiyah schools in Kartasura participated in this community service. They have technically trained with new experiences designing ethnomathematics-based students’ worksheets and developing ethnomathematics-based students’ worksheets in their selected topic; the participants were fully engaged during the training. There were feedback and a necessity towards integrating cultural context in mathematics learning to improve. The results of the training show that 100% of the participants gave a score of 4 and 5 on a scale of 5 for the training carried out. In addition, the usefulness of the material and the quality of the presentation are also given the same value. Participants quite understand the material provided. This can be seen in the participants' understanding scores, 82.4% gave a score of 3 and 17.6% gave a score of 4. Abstrak. Pengabdian kepada masyarakat ini bertujuan untuk: (a) memperkenalkan cara mendesain Lembar Kerja Peserta Didik (LKPD) berbasis ethnomatematika pada pembelajaran matematika bagi guru SMP Muhammadiyah di kecamatan Kartasura; (b) mengadakan workshop dan melatih guru dalam mendesain LKPD berbasis ethnomatematika. Pelatihan dilakukan secara daring menggunakan Zoom meeting dan Schoology Learning Management System. Pesertanya adalah 17 guru dari beberapa SMP Muhammadiyah di Kartasura. Kegiatan pengabdian ini dilakukan melalui tahapan sebagai berikut: persiapan, terdiri dari koordinasi internal dan eksternal; tahap implementasi yang meliputi pengenalan dan pelatihan pengembangan LKPD berbasis ethnomatematika yang dirancang dalam pembelajaran matematika. Para guru telah dilatih secara teknis dengan pengalaman baru merancang LKPD berbasis ethnomatematika dan mengembangkan LKPD baru sesuai topik pilihan mereka; peserta terlibat penuh selama pelatihan. Ada umpan balik dan kebutuhan untuk peningkatan integrasi konteks budaya dalam pembelajaran matematika. Hasil pelatihan menunjukkan bahwa sebesar 100% peserta memberi nilai 4 dan 5 dalam skala 5 untuk pelatihan yang dilaksanakan. Selain itu, kemanfaatan materi dan kualitas presentasi juga diberi nilai yang sama. Peserta cukup memahami materi yang diberikan. Hal ini dapat dilihat pada skor pemahaman peserta, 82,4% memberi skor 3 dan 17,6% memberi skor 4.